Systematic Approach in Low Cost Housing: Design and Construction Strategies for Affordable Housing (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Low cost housing refers to those housing units which are affordable by that section of society whose income is below than median household income. Quantifying and maximizing occupants' comfort in low cost housing units is dependent on design and construction decisions that affect the occupants' thermal comfort, indoor air quality, and day lighting quality. This depends on three key parameters— income level, size of dwelling unit and affordability. This paper aims to point out the various aspects of predestined building methodologies by highlighting the different available techniques, and the economic advantages achieved by its adoption. In a building the walls, floors and roofs are the most important sections, which can be analyzed distinctively based on the needs, thus, improving the speed of construction and reducing the construction cost. This paper also aims to give the characteristic of low cost housing and also cover local materials in the different components of building to make them as low cost available solutions for low income groups.